PELAKSANAAN KERJASAMA INTERNATIONAL ORGANIZATION FOR MIGRATION (IOM) DAN INDONESIA DI KOTA PEKANBARU DALAM MEMBERIKAN PERLINDUNGAN TERHADAP PENGUNGSI ROHINGYA - Wahyuni, Nadana Tri; Saeri, Mhd. (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This research examines the collaboration carried out by the Pekanbaru City government with one of the international organizations that handles refugees, namely the International Organization for Migration (IOM) in providing protection for refugees. Protection for refugees, one of whom is the Rohingya ethnic group from Myanmar, has become one of the problems being faced. Indonesia's limited authority in handling refugees certainly requires cooperation with other parties, this is based on Indonesia not having ratified the 1951 Geneva Convention and the 1967 Refugee Protocol. This research uses qualitative methods, with data collection techniques sourced from literature, books, journals, papers, reports, news, articles, the internet, and interviews. This research uses the perspective of liberalism and international cooperation theory. The results of this research show that the collaboration carried out by the Pekanbaru City Government and IOM is based on the Pekanbaru Mayor's Decree Number 153 of 2023 concerning the Pekanbaru City Task Force for Handling Refugees from Abroad. Kesbangpol as the leading sector coordinates with other parties and IOM in providing Rohingya refugees with the right to health, education and also social welfare which has been implemented. Keywords: Refugees, Rohingya Ethnicity, Government, International Organization for Migration (IOM)